RNA-seq analysis of the salivary glands and midgut of the Argasid tick Ornithodoros rostratus - Araujo, Ricardo N. (Sci Rep, 2019)
Ornithodoros rostratus is a South American argasid tick which importance relies on its itchy bite and potential as disease vector. They feed on a wide variety of hosts and secrete different molecules in their saliva and intestinal content that counteract host defences and help to accommodate and metabolize the relatively large quantity of blood upon feeding. The present work describes the transcriptome profile of salivary gland (SG) and midgut (MG) of O. rostratus using Illumina sequencing. A total of 8,031 contigs were assembled and assigned to different functional classes. Secreted proteins were the most abundant in the SG and accounted for ~67% of all expressed transcripts with contigs with identity to lipocalins and acid tail proteins being the most representative. On the other hand, immunity genes were upregulated in MG with a predominance of defensins and lysozymes. Only 10 transcripts in SG and 8 in MG represented ~30% of all RNA expressed in each tissue and one single contig (the acid tail protein ORN-9707) represented ~7% of all expressed contigs in SG. Results highlight the functional difference of each organ and identified the most expressed classes and contigs of O. rostratus SG and MG.